THE GENUS PYCNOPORUS IN INDONESIA - Dewi Susan; Fandri Sofiana Fastanti; Sutikno Sutikno; Yayan Supriyanti; Yayah Robiah; Nira Ariasari Z (Floribunda, 2021)
The genus Pycnoporus is a member of Phylum Basidiomycota. This fungus is one of polypore genera that is easily recognized from the orange color of the fruiting body and it likely has high morphological features. Currently, there are 207 number fungal specimens kept in Herbarium Bogoriense (BO) under the genus Pycnoporus, and they were identified as P. sa-nguineus (L.) Murrill, P. cinnabarinus (Jacq.) P. Karst., and Pycnoporus sp. To ensure that those species name of the Pycnoporus collections is correct, thus this study was carried out.  Re-identification process on the fungal collections was done based on macro-micromorphological features of all Pycnoporus specimens. This study revealed that species Pycnoporus collections stored in BO represent 2 species: P.sanguineus (L.) Murrill and P. puniceus (Fr.) Ryvarden. In addition, some specimens under the name P. cinnabarinus should be validated as P. puniceus. This information will be very useful for fungal taxonomists, non-taxonomists, and people who work on Pycnoporus species from Indonesia.